2000
DOI: 10.1046/j.1442-200x.2000.01230.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for nutritional rickets among children in Kuwait

Abstract: Nutritional rickets is a multifactorial condition. However, several factors seem to make important contributions. Among these, lack of exposure to sunlight, prolonged breast feeding without supplementation and inadequate weaning practices are important. Maternal education is important as it can influence all of the above factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(35 citation statements)
references
References 6 publications
2
32
1
Order By: Relevance
“…21 Regarding sunlight exposure similar results was obtained from many studies which showed that lack of sunlight exposure increases the risk of rickets (Majeed et al, Mastsuo et al; Molla et al). [22][23][24] Our clinical findings were comparable to study carried out by Onyiriuka et al were lower limb deformity was commonest clinical feature followed by wrist widening. 18 Another study from Karachi reported that most common clinical presentation was rachitic rosary (87%) followed by wrist widening (76%).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…21 Regarding sunlight exposure similar results was obtained from many studies which showed that lack of sunlight exposure increases the risk of rickets (Majeed et al, Mastsuo et al; Molla et al). [22][23][24] Our clinical findings were comparable to study carried out by Onyiriuka et al were lower limb deformity was commonest clinical feature followed by wrist widening. 18 Another study from Karachi reported that most common clinical presentation was rachitic rosary (87%) followed by wrist widening (76%).…”
Section: Discussionsupporting
confidence: 88%
“…Children developing rickets are often pale, irritable, and sleepless and perspire profusely. 5 It is manifested by widening (flaring) of metaphysis of long bones, prominence of costochondral junction (rachitic rosary), flaring of lower anterior thoracic wall and frontal bossing. After the child begins to walk and bear weight, genu valgum or genu varum develops.…”
Section: Introductionmentioning
confidence: 99%
“…These countries have experienced rapid economic and social changes during the past two decades, resulting in a marked improvement in lifestyle and health status (6)(7)(8)(9)(10)(11) . However, these rapid changes have led to the development of a paradoxical situation regarding nutrition, in that both a lack of and an excess of nutrition coexist.…”
mentioning
confidence: 99%
“…However, these rapid changes have led to the development of a paradoxical situation regarding nutrition, in that both a lack of and an excess of nutrition coexist. Undernutrition has manifested as growth retardation/bone deformity among pre-school children and Fe-deficiency anaemia, while overnutrition has manifested as obesity, dental caries and non-communicable disease (5,(7)(8)(9)(10)(11) .…”
mentioning
confidence: 99%
“…This study found that there is significant association between rickets and sunshine exposure status (p=0.000) indicating higher prevalence of rickets in children with no sun shine exposure which is comparable with a case control study carried out in Kuwait. This is because vitamin D production in the skin is by product of sun shine exposure [8].…”
Section: Discussionmentioning
confidence: 99%